Experimental and Computational Studies on the Reactivity of Methanimine Radical Cation (H2CNH+•) and its Isomer Aminomethylene (HCNH2+•) With C2H2 - Richardson, Vincent; Ascenzi, Daniela; Sundelin, David; Alcaraz, Christian; Romanzin, Claire; Thissen, Roland; Guillemin, Jean-Claude; Polášek, Miroslav; Tosi, Paolo; Žabka, Jan; Geppert, Wolf D. (Frontiers in Astronomy and Space Sciences, 2021)
Experimental and theoretical studies are presented on the reactivity of the radical cation isomers H2CNH+. (methanimine) and HCNH2+. (aminomethylene) with ethyne (C2H2). Selective isomer generation is performed via dissociative photoionization of suitable neutral precursors as well as via direct photoionization of methanimine. Reactive cross sections (in absolute scales) and product branching ratios are measured as a function of photon and collision energies. Differences between isomers’ reactivity are discussed in light of ab-initio calculations of reaction mechanisms. The major channels, for both isomers, are due to H atom elimination from covalently bound adducts to give [C3NH4]+. Theoretical calculations show that while for the reaction of \HCNH2+. with acetylene any of the three lowest energy [C3NH4]+ isomers can form via barrierless and exothermic pathways, for the H2CNH+.reagent the only barrierless pathway is the one leading to the production of protonated vinyl cyanide (CH2CHCNH+), a prototypical branched nitrile species that has been proposed as a likely intermediate in star forming regions and in the atmosphere of Titan. The astrochemical implications of the results are briefly addressed